PENJADWALAN OPTIMAL OPERASI UNIT – UNIT PEMBANGKIT UNTUK MEMENUHI KEBUTUHAN BEBAN DITINJAU DARI PEMAKAIAN BAHAN BAKAR - Agusthinus S. Sampeallo (Universitas Nusa Cendana, 2012)
Diesel Power Plant (Diesel) is one of the plants that use fuel oil to generate electricity. Because of the high price of fuel, it is necessary to schedule the operation of the generating units, so that in addition of generating electrical power quality in accordance with the needs also fuel consumption can be optimized. Optimal scheduling of generating units can be done by selecting a combination of operating generating units which produce a certain power and the least fuel consumption as a first priority to operate.This study aims to examine the optimization of fuel consumption in Diesel Kefamenanu. By calculating the Incremental Rate of generating units that exist by using algebraic methods, it can show the optimal combination of operating generating units and how much the fuel consumption of the combined operation of the plant units.